Antioxidant Activity Comparison of Jamu Cekok and Its Individual Herbal Components Using the DPPH Method - Lusi Lusi; Puji Astuti; Meri Ropiqa; Virhan Novianry (Biology, Medicine, & Natural Product Chemistry, 2026)
Jamu cekok is a traditional Indonesian herbal drink commonly consumed by children to increase appetite. It is made from a combination of several plants, including Curcuma zanthorrhiza (C. zanthorrhiza), Curcuma longa (C. longa), Zingiber officinale (Z. officinalle), and Kaemferia galanga (K. galanga). The combination of these plants potentially enhanced the antioxidant effects due to the synergism or antagonism interaction among the constituent herbs. This research aimed to determine the antioxidant activity of jamu cekok and compare it with the antioxidant activity of its individual herbal components. Methods were started with the extraction of jamu cekok using ethanol as the solvent, prepared from a 1:1:1:1 ratio of C. zanthorrhiza, C. longa, Z. officinale, and K. galanga extract. The resulting extracts were tested using a 1,1-diphenyl-2-picrylhydrazyl (DPPH) scavenging assay and phytochemical screening. Analysis revealed that jamu cekok extract contains alkaloids, flavonoids, and saponins. Turmeric, ginger, and galangal exhibited strong antioxidant activity with IC50 values of 96.158 ppm, 87.040 ppm, and 83.855 ppm, respectively. Curcuma showed moderate antioxidant activity with an IC50 value of 112.227 ppm. Jamu cekok exhibits very strong antioxidant activity (IC50 = 46.904 ppm), surpassing the activity of its individual herbal components. The synergistic interaction among bioactive compounds, particularly alkaloids, flavonoids, and saponins, is presumed to contribute to the enhanced antioxidant potential of jamu cekok. These results support its role as a natural antioxidant source and provide a scientific basis for its traditional use in health promotion.